Three-dimensional plasmonic nanoclusters - Nordlander, Peter (2013)
Assembling nanoparticles into well-defined structures is an important way to create and tailor the optical properties of materials. Most advances in metamaterials research to date have been based on structures fabricated in two-dimensional planar geometries. Here, we show an efficient method for assembling noble metal nanoparticles into stable, three-dimensional (3-D) clusters, whose optical properties can be highly sensitive or remarkably independent of cluster orientation, depending on particle number and cluster geometry. Some of the clusters, such as tetrahedra and icosahedra, could serve as the optical kernels for metafluids, imparting metamaterial optical properties into disordered media such as liquids, glasses, or plastics, free from the requirement of nanostructure orientation.